APPLICATION OF LEGAL SANCTIONS FOR PERSECUTION IN THE PERSPECTIVE OF NATIONAL CRIMINAL LAW AND ISLAMIC CRIMINAL LAW - Sardi; M. Rafandy Harahap; Stephen Martin (PT. Radja Intercontinental Publishing, 2023)
This research uses a type of library research or normative legal research, with the data sources used being secondary data in the form of the Criminal Code and Jinayah Fiqh books. Data collection was carried out by reading various forms of books and literature that were relevant to the case. The conclusion of this thesis can show that national law in Indonesia does not specifically regulate punishments for perpetrators of persecution, but perpetrators can be charged with the same punishment as acts of persecution, namely the articles in the Criminal Code (KUHP). Perpetrators of persecution are usually charged with extortion and threats, abuse and assault. Meanwhile, according to Islamic law, persecution is included in the form of extortion (hirabah) and also the form of persecution (jurh), the perpetrator himself is punished with a qishas penalty if it results in death and a ta'zir penalty if only minor injuries occur. However, Allah SWT strictly forbids this act and must be avoided by us as His creatures.